Effect of COVID 19 pandemic on time to care, use of ambulance, admission characteristics, demography, injury characteristics, management and outcome of Paediatric Orthopaedic trauma patients admitted to the trauma centre - Bharat, Abhinav; Verma, Vikas; Afaque, Syed Faisal; Raikwar, Archana; Chand, Suresh; Singh, Ajai (Indian Journal of Community Health, 2022)
Background: Lockdown imposed to limit the spread of COVID 19 may have had a significant effect on the time to care, demography, injury causation, injury characteristics, volume and nature of admission, management and outcome of paediatric orthopaedic trauma patients. Objective: To document the effect of lockdown on the time to care at KGMU, use of ambulance, volume and type of admissions, demography, injury causation, injury characteristics, management and outcome of paediatric orthopaedic trauma patients. Methods:. This record review compared age, sex, type of admission, mechanism of injury, injury characteristics, type of treatment, vehicle used for transport, and outcome among patients admitted in pre-lockdown, lockdown and post lockdown. Results: Lockdown was associated with decrease in the number of cases (p<0.01), increase in the time since injury to reception (p<0.040), a rise in the share of referred admission (p<0.040), time since reception at KGMU, time to definitive care (p<0.001), high energy falls (p<0.001), injuries at home (p<0.001), higher ISS (p<0.001), non operative treatment (p=0.038) and greater use of ambulance (p=0.003). Conclusion: Lockdown resulted in a significant change in the causation and management of injury, significant delays in timeliness of care, reduction in the volume of admissions, an increase in injury severity and share of referral admissions.